2013
DOI: 10.1007/s10551-013-1888-7
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Environmental Responsibility in Polluting Industries: Does Religion Matter?

Abstract: 本文基于手工搜集的、2008-2010年期间污染行业的A股上市公司环境责任与佛教的相关数据,实证分析了中国佛教是否、以及如何影响公司的环境绩效。研究发现,佛教与公司环境绩效显著正相关,但法律环境调和了佛教与公司环境绩效之间的正相关关系。这一研究,为宗教与社会责任行为、特别是环境责任提供了重要的经验证据支持。Using a sample of Chinese listed firms in polluting industries for the period of 2008–2010, we empirically investigate whether and how Buddhism, China’s most influential religion, affects corporate environmental responsibility (CER). In this study, we measure Buddhist variables as the number of Buddhist monasteries within a certain radius around Chinese liste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
216
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 262 publications
(259 citation statements)
references
References 68 publications
9
216
0
Order By: Relevance
“…However, they cannot have completely coincident registered addresses. Therefore, following Du et al (2013b), we can obtain religious variables in the strict sense when we adopt the reciprocal value of the distance between a listed firm and a specific number of religious sites as the positive proxy for religion.…”
Section: Robustness Checks Using Other Measures Of Religionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they cannot have completely coincident registered addresses. Therefore, following Du et al (2013b), we can obtain religious variables in the strict sense when we adopt the reciprocal value of the distance between a listed firm and a specific number of religious sites as the positive proxy for religion.…”
Section: Robustness Checks Using Other Measures Of Religionmentioning
confidence: 99%
“…To sum up, Du (2013a, b) establishes the link between religion and corporate governance, especially owner-manager agency conflicts and agency costs between the controlling shareholder and minority shareholders. Du et al (2013a) find that religion has positive impact on corporate philanthropic giving and Du et al (2013b) find that religion is associated with corporate environmental responsibility. follow Du (2013a, b) and utilize quasi-firm-level religion variables, but also develop Du (2013a)'s approach to adopt firm-level religion variables in the strict sense to provide robust results.…”
Section: Introductionmentioning
confidence: 98%
“…The government's conflicting goals of high economic growth and environmental conservation have created a dilemma [1]. Overextended resources and polluted air, soil, and water have cast a horrific shadow over China.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of literature (see, for example, Barro & McCleary, 2003;Guiso, Sapienza, & Zingales, 2003;Kuran, 2009;Du et al, 2014) has identified the need to examine religion in corporations.…”
Section: Does the Degree Of Religiosity In An Institutional Environmementioning
confidence: 99%